Injuries and Illnesses During the 53rd FIS Nordic World Ski Championships 2021 in Oberstdorf: A Prospective Cohort Study. Issue 2 (22nd March 2023) - Kastner, Tom; Junge, Astrid; Weith, Moritz; Porzig, Florian; Disch, Alexander C.; Edouard, Pascal; Wolfarth, Bernd; Hollander, Karsten
Abstract : Objective: For the 3 Nordic ski disciplines of cross-country skiing, Nordic combined, and ski jumping, data on injuries and illnesses during major sporting events only exist from the Winter Olympics of 2010 to 2018. So far, an investigation has not been conducted during the Nordic World Ski Championships. Design: Prospective cohort study. Setting: Fédération Internationale de Ski (FIS) Nordic World Ski Championships 2021 in Oberstdorf, Germany. Participants: Overall, 663 athletes from 65 nations participated in the FIS Nordic World Ski Championships 2021. The study population included 344 athletes from 32 nations. Interventions: National medical teams were invited to report daily all newly incurred or exacerbated injuries and illnesses. Main Outcome Measures: All reported injuries and illnesses that occurred during the championships from February 23 until March 7, 2021, were analyzed. Injury and illness rates were calculated with 95% confidence intervals (95% CIs). Results: The 32 reporting nations returned 88.4% of the daily report forms. The incidence of injuries was 4.7 (95% CI, 2.4-6.9) per 100 athletes in the 3 Nordic ski disciplines. The incidence of illness was also 4.7 (95% CI, 2.4-6.9) per 100 athletes with a relative proportion of infection-related illnesses of 31.3%. Conclusions: Although the incidence of injuries of the Nordic disciplines was comparable with those of the 2010 to 2018 Winter Olympics, the incidence of illnesses was lower than during the previous 3 Winter Olympic Games with a lower rate of infection-related illnesses. This might be caused by the high hygiene measures due to the coronavirus disease 2019 pandemic.